THE APPLICATION OF SIX SIGMA TO IMPROVE THE YIELD OF PLASTIC INJECTION MOLDING - Hsiao, Chun Tze; Lin, Chih-Ping; Fan, Ping-Hsin (The South African Journal of Industrial Engineering, 2023)
Plastic injection molding has complex process parameters. The Six Sigma improvement method mainly uses quality control and statistical methods to improve product quality, so as to reduce the cost and waste caused by defective products. Taiwan is the world leader for original equipment manufacturing in the laptop industry, and related peripheral accessories are also a major concern of customers. The subject of this study was a professional supplier of laptop batteries. Through the collection of customer complaint data, it was found that battery case deformation was the most important problem for customers. Therefore, in order to remain competitive, the battery case deformation problem needed to be overcome first. Enterprises need to improve their existing processes to reduce the rate of product defects, improve output efficiency and product quality, and reduce production costs, so as to improve their competitiveness in the industry.This study took a Taiwanese company as an example to improve the plastic injection process through the improvement steps of Six Sigma. In this process, two key process factors, namely the injection speed and the cooling time, were identified by analytical tools. After calculating customers’ daily product demand, the most suitable parameters were found using the ‘design of experiments’ method. The results showed that the process capacity and product yield could be significantly improved. The key to the success of this Six Sigma project was the project implementer’s design of the experiment.